Effectiveness of Cropping Systems in Mitigation of Climate Change through Carbon Sequestration - Prakash, Ved; Singh, A. K.; Kumar, Santosh; Dwivedi, S. K. (Indian Farming, 2015)
Increased concentrations of GHGs and the overall warming of the atmosphere has resulted in changing rainfall patterns, disruption in hydrological cycles, melting of glaciers and rise in sea levels. These have in turn had serious impact on sustainability of water resources, agriculture, forests and ecosystems, affecting the well being of billions of people on earth. The cropping systems and the management practices that could provide carbon input higher than the above critical level are likely to sustain the SOC level and maintain soil health in the Indian subcontinent.